PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA IPAS KELAS IV DI SD NEGERI 071218 FONDAKORAYA KABUPATEN NIAS SELATAN - Mitra Wati Ndruru; Bogor Lumbanraja; Eka Margareta Sinaga; Regina Sipayung; Juliana; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the influence of the Problem Based Learning model on the science learning outcomes of fourth-grade students at SD Negeri 071218 Fondakoraya, South Nias Regency, for the 2024/2025 academic year. This research employed a quantitative research method and a pre-experimental research design. The population of this research was all fourth-grade students at SD Negeri 071218 Fondakoraya. The sample was selected using saturated sampling, where all 30 fourth-grade students at SD Negeri 071218 Fondakoraya were included as the sample. To ascertain the students' initial abilities, the researcher conducted a pre-test with an average score of 45.56, which falls into the